2005
DOI: 10.2106/jbjs.e.00347
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Transplantation in Symptomatic Patients Less Than Fifty Years Old

Abstract: The short-term results of meniscal transplantation are encouraging in terms of reducing knee pain and increasing function; however, long-term transplant function and any chondroprotective effects remain unknown and require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(154 citation statements)
references
References 11 publications
3
145
2
4
Order By: Relevance
“…Um die Erfolgsaussichten der FLOCSAT zu verbessern, ist es notwendig, dass vorbestehende signifikante rotatorische und translationale, gerade Instabilitäten identifiziert und je nach Grad der Pathologie simultan oder zweizeitig entweder mittels eines L-FLOCSAT oder bandrekonstruierender Maßnahmen korrigiert werden [21]. …”
Section: Bandverletzungenunclassified
“…Um die Erfolgsaussichten der FLOCSAT zu verbessern, ist es notwendig, dass vorbestehende signifikante rotatorische und translationale, gerade Instabilitäten identifiziert und je nach Grad der Pathologie simultan oder zweizeitig entweder mittels eines L-FLOCSAT oder bandrekonstruierender Maßnahmen korrigiert werden [21]. …”
Section: Bandverletzungenunclassified
“…In general, the results of MAT associated with anterior cruciate ligament reconstruction or cartilage repair/ restoration are not worst compared to isolated MAT [6][7][8]. MAT and associated cartilage procedures (autologous chondrocyte implantation, osteochondral allograft, osteochondral autograft or microfractures) essentially provide similar improvement in pain relief, KOOS score, IKDC score (subjective), Noyes score, Tegner score, and sports level compared to isolated MAT [15,32,34,69,70]. Only Lysholm and modified Cincinnati scores were lower in the combined compared to isolated MAT [71,72].…”
Section: Associated Proceduresmentioning
confidence: 99%
“…The failure rate for medial allograft is higher compared to the lateral allograft [29]. Noyes et al observed a different timing of graft failure in the lateral (mean of 53 months) and medial (mean of 25 months) menisci [34]. The most common complications for MAT are: graft tear, graft shrinkage, graft extrusion, knee stiffness (especially if MAT with associated procedures), infection, immune reaction, suture granulomas, portal pain, synovitis, and intraarticular hematoma [6,7,13,16,35,36].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, HTO has also become very popular is association with cartilage techniques and meniscal grafts (Noyes et al, 2004). In the past chronic knee instability and varus thrust have been considered a contraindication for HTO (Coventry et al, 1993;Naudie et al, 1999), but nowadays, chronic instability is an indication for HTO, because allows to correct both the coronal and the sagittal alignment, improving the function of an unstable knee.…”
Section: Introductionmentioning
confidence: 99%